Preventive Care for Diabetic Foot Ulcers: Application of Peplau’s Theory of Interpersonal Relations - Choochuen, Wandee; Kunlaka, Suthanan; Sarakshetrin, Atiya; Rattanapark, Pacharanan (Nursing Research and Innovation Journal, 2021)
Abstract: People with diabetes are at high risk of foot ulcers due to atherosclerotic vascular disease and nerve damage from poor blood flow or changes in the shape of feet.Weakness in the foot can cause foot deformities, numbness, cracks, and foot ulcer,leading to foot amputation. Therefore, preventive care for people with diabetes is important to avoid diabetic foot ulcers. This article aims to present knowledge about preventive care for diabetic foot ulcers by applying Peplau’s Theory of Interpersonal Relations, a case study and nurses’ roles. Peplau’s Theory of Interpersonal Relations is applied to raise awareness of persons with diabetes towards foot care and their potential in preventing long-term complications of diabetic foot ulcers. Keywords: Peplau’s Theory of Interpersonal Relations, Diabetic foot ulcer, People with diabetes, Nurse’s roles